Hematúria enzoótica bovina : detecção do papilomavírus tipo 2 pela técnica de Reação em Cadeia de Polimerase PCR - Dias, Jacques Douglas Coimbra (2010)
The bovine enzootic hematuria (BEH) is a disease of worldwide occurrence and presents a varied prevalence in endemic areas, which can reach 90% in animals older than two years. The technique of polymerase chain reaction (PCR) was developed and standardized for the detection of bovine papillomavirus type 2 (BPV-2). This technique was based on enzymatic amplification of a fragment of 386 bp highly conserved gene. Infection with bovine papillomavirus type 2 (BPV-2) has also been implicated in the etiology of this disease. The objective of this study make a macroscopic lesions of bovine bladder and the presence of human papillomavirus type 2 by the technique of polymerase chain reaction - PCR. For this 50 bladders were collected from cattle with gross lesions, each being divided into four quadrants, referenced in the body for cuts such as A, B, C and D, for histopathologic evaluation. The characterization included the definition of macroscopic types of lesions: focal or diffuse hemorrhages, lesions or verrucous hemangiomas ulcerated lesions, among others. Histopathologic analysis showed five samples positive for cancer (2.5%). The method of polymerase chain reaction, all samples were considered malignant and showed the bovine papillomavirus type 2. The presence of bovine papillomavirus type 2 in neoplastic lesions of the urinary bladder of cattle, confirmed by PCR indicates that this virus may be directly involved in the pathogenesis of bovine enzootic hematuria (BEH) in association with the consumption of the fern, and one plant endemic in the region